1989
DOI: 10.1051/parasite/1989644268
|View full text |Cite
|
Sign up to set email alerts
|

Étude de quelquesLitomosoidesparasites de rongeurs ; conséquences taxonomiques

Abstract: The type species of the genus Litomosoides, L. sigmodontis, and L. carinii are two distinct species. As a result, the filaria which is widely used in drug trials has to be reinstated sigmodontis and not carinii.With the exception of the two parasite species of Geomyid rodents, which show affinities with the genus Litomosa, the species of Litomosoides may be devided into two groups, principally 1. Ce travail a été effectué grâce à la subvention F3/181/18 (A) de l'Organisation Mondiale de la Santé.Laboratoire Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 7 publications
2
66
0
2
Order By: Relevance
“…Recently, we have found that Litomosoides galizai Bain Bain et al, 1989). The observation that L. sigmodontis can undergo complete deve lopment in the mouse is not new (1, 4) but possibly due to greater interest shown in Brugia spp., the seminal works of Hawking and Burroughs (1) and Patra and Basu (4) have been largely forgotten.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have found that Litomosoides galizai Bain Bain et al, 1989). The observation that L. sigmodontis can undergo complete deve lopment in the mouse is not new (1, 4) but possibly due to greater interest shown in Brugia spp., the seminal works of Hawking and Burroughs (1) and Patra and Basu (4) have been largely forgotten.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect that contributes to this finding is that Litomosoides uses an ectoparasite as vector (BAIN et al, 1989), and that both hosts could share ectoparasites.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, two species of Litomosoides showed a close relationship to our material, but they differ in certain aspects. The first was L. kohnae (= L.carinii SENSU Vaz, 1931) Bain et al (1989), which presents a right spicule that is not well esclerotized. The right spicule's distal region is cone shaped, sustained by two thin cuticular sticks, ending in a short membranous thong-like structure, generally folded dorsally in the spicule; the tail is often slightly projected.…”
Section: Discussionmentioning
confidence: 99%
“…Bain et al (1989) consideram a cápsula bucal reduzida com seus diferentes tipos de espessamentos nas laterais como o caracter morfológico mais importante para diferenciar espécies desse gênero.…”
Section: Discussionunclassified
“…Bain et al (1989) colocam a espécie dentro do grupo carinii caracterizado pelo espículo direito esclerotizado até a extremidade distal, com capa terminal e lâmina do espículo esquerdo simples, sem grandes asas longitudinais membranosas.…”
Section: Discussionunclassified